Leo Grebler, Mexican Immigrants to the United States : The Record and its Implications. Mexican-American Study Project, Advance Report 2 Los Ángeles, University of California, 1966. xxx, 519 p. - Pedrero, Mercedes (Estudios Demográficos y Urbanos, 1968)
LEO GREBLER, Mexican Immigrants to the United States: The Record and its Implications. Mexican-American Study Project, Advance Report 2. Los Ángeles, University of California, 1966.